YOUTH HOMELESSNESS IN CROATIA: PATHWAYS, CHALLENGES, AND SUPPORT SYSTEMS - Kletečki Radović, Marijana; Rukavina Lapov, Ela (International Journal of Child, Youth and Family Studies, 2025)
Youth homelessness is a complex issue. The experience of living in alternative care, combined with a lack of support, is a key risk factor that increases the likelihood of youth becoming homeless. This study aimed to explore the lives of homeless youth through their personal experiences, focusing on their pathways to homelessness and the support they would have required to avoid it. Qualitative research was conducted with six young people aged 15 to 29 who were homeless and residing in a shelter in Zagreb. Data were collected through semi-structured interviews and analyzed using a thematic analysis approach. The results showed that the participants all had a background in alternative care, often with multiple placements while in care. Key factors contributing to homelessness included aging out of the care system, broken family relationships, mental health issues, and unemployment. The findings showed that these young homeless individuals primarily relied on formal support systems. They emphasized the need for practical assistance, access to social welfare assistance, professional support and empowerment, and emotional support from trusted individuals. This research underscores the importance of providing targeted, systematic, support to help young homeless people overcome the challenges they face on their path to a stable and independent life.